Improvement in the tensile strength of epoxy resin and hemp/epoxy resin composites using carbon nanotubes - Longkullabutra H. (2014)
An experimental was investigated the condition of reinforcement of epoxy resin and hemp fiber/epoxy resin composites with carbon nanotubes (CNTs). The CNTs adding nanopowder were vibrated via the vibration milling technique for 6-48 h. Different volume percentages of CNTs were dispersed for hemp/epoxy resin composites. To compare properties of composites sample, CNTs were also added into epoxy resin for reference. Tensile strength of both specimens was tested. The significantly adding of CNTs and its dispersion in polymer matrix were investigated by scanning electron microscope (SEM). The results indicate that adding the milled CNTs can improve tensile properties of composites. © (2010) Trans Tech Publications.